Descriptions of Leptolaimus sinensis sp. nov. and Perspiria brevicaudata sp. nov. (Nematoda) from the Yellow Sea, China - Chu, Mengdi; Hao, Yingdong; Huang, Yong (Zootaxa, 2023)
Two new free-living marine nematodes which were collected at silt beach of Rizhao along the Yellow Sea are identified here as Leptolaimus sinensis sp. nov. and Perspiria brevicaudata sp. nov. Leptolaimus sinensis sp. nov. is characterized by annulated cuticle with lateral alae, 2 µm in width; buccal cavity cylindrical; cephalic setae 2 µm long; amphidial fovea unispiral, circular in outline; six to seven evenly spaced tubular precloacal supplements and 23–29 continuous alveolar supplements extending from cloaca to level of the base of buccal cavity; spicules slender, slightly arcuate; gubernaculum with dorso-caudal apophysis; tail conico-cylindrical, about 6 times cloacal body diameter in males and elongated in females, about 9 times anal body diameter in length. Perspiria brevicaudata sp. nov. is characterized by having four cephalic setae and four cervical setae; small buccal cavity with dorsal tooth and minute ventral tooth; amphidial fovea unispiral, looking like double circle in outline, surrounded partially by cuticle striations; spicules arcuate with ventral velum, handle-like proximally and tapered distally; gubernaculum plate-shaped, without apophysis; twelve winged precloacal supplements present. Updated identification keys for group of Leptolaimus species characterized by the presence of both alveolar and tubular precloacal supplements and for species of Perspiria are also given.